PENGARUH KUALITAS PELAYANAN, KEPUASAN NASABAH, KUALITAS PRODUK TERHADAP LOYALITAS NASABAH DI BANK PANIN PELITA - Natalia; Hazriyanto (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The purpose of this study was to determine the quality of service, customer satisfaction, product quality on customer loyalty at Bank Panin Pelita ". This study took a sample of 54 respondents. Source of data is primary data with data collection method using Likert scale questionnaire scale. By using simple random sampling to determine the respondents’ responses to each variable. The data analysis technique used is descriptive analysis and path analysis. The results of the path analysis show that product quality and service quality have a significant effect on customer loyalty, while service quality on customer satisfaction and customer satisfaction on customer loyalty has no significant effect. Because the value of t-statistics is not above the t-table (t-table with a significance of 5% and DF = 54, is 2.0048793). The results of testing the parameter coefficient of customer satisfaction on customer loyalty is 0.1014, service quality to customer satisfaction is 0.2263, product quality to customer loyalty is 0.3086 and service quality to customer loyalty is 0.3792